Reuse of oil and gas produced water for irrigation of spring wheat (Triticum aestivum L.): plant physiological and immune system response - Qiu, Yuheng, author; Borch, Thomas, advisor; Blotevogel, Jens, committee member; Young, Robert, committee member (Colorado State University. Libraries, 2019)
Water resources for agricultural irrigation in the semiarid western United States are challenged due to increased oil and gas (O&G) activity and increasing water scarcity. Produced water (PW) generated from the O&G industry has been considered as an alternative source for crop irrigation, but there are few studies on the topic. Thus, here a greenhouse study was conducted to evaluate the impacts of PW irrigation on spring wheat (Triticum aesticum L.) with respect to plant morphology, physiology, and immunity to bacterial and fungal pathogens. Plants were irrigated with the following types of water: 100% tap water (TW), 10% and 50% PW (PW10 & PW50) and a salt (NaCl) solution (SW50 control; NaCl concentration is equal to PW50). Furthermore, pathogen treatments containing bacteria (Xanthomonas campestris) and fungi (Septoria tritici) were applied to the wheat plants to test plant immune response. In comparison with the TW control, plants irrigated with PW50 exhibited developmental delay and premature senescence, significant loss of yield, and significant decline in photosynthetic efficiency and immune function. The PW10 and SW50 control both resulted in reduced plant yield and photosynthesis, but PW10 was more damaging than SW50 to plant immune system, despite the high salt contents in SW50. These findings indicate that constituents (e.g., organic contaminants) other than NaCl in PW are contributing to plant stress, and they may play a far greater role in affecting plant immune function than salt stress.
Keywords: immune system; agricultural irrigation; water reuse; produced water; Triticum aestivum